2014
DOI: 10.1002/stem.1729
|View full text |Cite
|
Sign up to set email alerts
|

Do Cryopreserved Mesenchymal Stromal Cells Display Impaired Immunomodulatory and Therapeutic Properties?

Abstract: We have recently reported that therapeutic mesenchymal stromal cells (MSCs) have low engraftment and trigger the instant blood mediated inflammatory reaction (IBMIR) after systemic delivery to patients, resulting in compromised cell function. In order to optimize the product, we compared the immunomodulatory, blood regulatory, and therapeutic properties of freeze-thawed and freshly harvested cells. We found that freeze-thawed MSCs, as opposed to cells harvested from continuous cultures, have impaired immunomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
266
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(294 citation statements)
references
References 43 publications
15
266
3
Order By: Relevance
“…In support of this, we have found that thawing induces 29) . This is the first translational evidence, which demonstrate the clinical benefit of using fresh MSCs .…”
Section: Mscs Display Impaired Responsiveness To Ifnγ Stimulationsupporting
confidence: 71%
“…In support of this, we have found that thawing induces 29) . This is the first translational evidence, which demonstrate the clinical benefit of using fresh MSCs .…”
Section: Mscs Display Impaired Responsiveness To Ifnγ Stimulationsupporting
confidence: 71%
“…3,33,34 In contrast, other studies 10,[35][36][37] have demonstrated that cryopreserved MSC exhibit equivalent viability and immunosuppressive potential to freshly isolated MSC from cell culture. Consistent with these findings, we found that freeze-thawed MEP displayed a viability of 95% and retained the ability to effectively suppress lymphocyte proliferation in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…Several reports show that cryopreservation reduces the immunomodulatory capacity of MSCs. 18,19 On the other hand, cryopreservation does not alter the surface marker profiles and osteogenic potential of BM-MSCs or compromise the therapeutic effects on cardiac function after direct intramyocardial injection. 20,21 Difference in donors or the cultivation period after cell thawing might affect the characteristics of MSCs.…”
Section: Discussionmentioning
confidence: 99%